Leitura recombinativa de palavras de inglês com onset e rime em braille e alfabeto romano em relevo por cegos - FEITOSA, Maria de Belém Rolla Bôas (Universidade Federal do Pará, 2014)
Studies have documented that the explicit teaching of discrimination of syllables promotes the emergence of reading of taught syllables, syllables with recombination of the letters of the taught syllables and the reading of words formed by taught and recombined syllables. Research on recombinative reading in English has demonstrated the emergence of reading of new words formed by the recombination of onset e rime. The present study investigated if the teaching of reading monosyllabic words formed by recombination among onset and rime promote reading of new English words in Braille code and Roman alphabet in raised letters to blind people. Three blind adults participated in the study that was divided in three stages. In Stage I, the participants were exposed to a pretest, three sequences of gradual teaching units of conditional discrimination interspersed with textual reading tests of training and generalization words. In Stage Ic it was applied a test of conditional discrimination among words printed in braille and words in Roman alphabet printed in raised letters. In Stages II and III, tests of textual reading of simple generalization words (Stage II) and compound words (Stage III) and the naming of objects were applied. After that, the relations AB (spoken words – objects), AC, AD (spoken words – printed words), BC, BD (objects – printed words) e CB, DB (printed words – objects) were tested. These relations have documented reading comprehension. After the equivalence tests, it was also verified the emergency of performance in copy and dictation. The words were printed in braille in Stages Ia, IIa e IIIa. The words in Roman alphabet were printed in raised letters in Stages Ib, IIb, and IIIb. All participants reached immediately the criterion in all or in most stages of teaching and test. All participants have presented both textual reading and reading comprehension of simple generalization words and compound words, printed in braille and Roman alphabet in raised letters. The results showed the emergence of recombinative reading after the teaching of conditional discrimination of monossilabic words formed by onset and rime.